Bioinspired and biomimetic cancer-cell-derived membrane nanovesicles for preclinical tumor-targeted nanotheranostics - Prasad, Rajendra (2023)
Funding Information: J.C. and B.M. acknowledge European Research Council grant agreement 848325 . R.P. would like to thank the Director, Indian Institute of Technology (BHU), Varanasi and the School of Biochemical Engineering, IIT (BHU) for support during preparation of this manuscript. We thank the Trident Diagnostics Center and staff for imaging and laser studies and NCCS, Pune for in vivo facilities. We would like to thank Prof. Rohit Srivastava and Dr. Sumit for their kind support. We extend our thanks to the School of Biotechnology and Kalinga Institute of Medical Sciences, KIIT, Institute of Eminence, Bhubaneswar. We dedicate this article to the memory of the late Prof. Sanjiv Sam Gambhir, a molecular imaging scientist. Figures/schemes were created with BioRender . Funding Information: J.C. and B.M. acknowledge European Research Council grant agreement 848325. R.P. would like to thank the Director, Indian Institute of Technology (BHU), Varanasi and the School of Biochemical Engineering, IIT (BHU) for support during preparation of this manuscript. We thank the Trident Diagnostics Center and staff for imaging and laser studies and NCCS, Pune for in vivo facilities. We would like to thank Prof. Rohit Srivastava and Dr. Sumit for their kind support. We extend our thanks to the School of Biotechnology and Kalinga Institute of Medical Sciences, KIIT, Institute of Eminence, Bhubaneswar. We dedicate this article to the memory of the late Prof. Sanjiv Sam Gambhir, a molecular imaging scientist. Figures/schemes were created with BioRender. J.C. and R.P. conceived the idea. M.G. G.C.K. R.P. and J.C. designed the experiments. M.G. G.C.K. R.P. and N.G. performed in vivo imaging and therapeutics studies. B.P. and E.H.A.W. conducted the western blots. B.P. and H.Q. performed the simulation studies. R.P. B.M. and J.C. wrote the paper. All authors contributed to final editing and multiple revisions of the present manuscript. J.C. is a co-founder and shareholder of TargTex S.A. R.P. is part of national and international patents related to lipid, gold, silica, and erythrocyte-based nanoparticles. Publisher Copyright: © 2023 The Author(s)